BRIDGING CULTURES ENRICHING ENGLISH LANGUAGE LEARNING THROUGH LOCAL HERITAGE - Nanda Pambudi; Meladina; Nurfitri; Fries Pileman Soa'e Sigilipu; Mike Nurmalia Sari; Lulu Jola Uktolseja (EDU RESEARCH, 2024)
This study explores the integration of local heritage into English language learning and its impact on motivation, cultural awareness, and linguistic competence. By employing a literature-based approach, the research investigates how heritage-based materials enhance learner engagement, foster cultural identity, and develop global communication skills. Key pedagogical strategies, including Content-Based Instruction (CBI), Project-Based Language Learning (PBLL), and technology-enhanced learning, are discussed to provide practical insights into curriculum development. The findings highlight the balance between preserving cultural identity and equipping learners for intercultural communication. This study concludes that heritage-based learning is a transformative approach to modern language education, emphasizing the need for inclusive, adaptable, and contextually rich instructional materials.